2019
DOI: 10.1101/863183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SAMHD1 is a key regulator of the lineage-specific response of acute lymphoblastic leukaemias to nelarabine

Abstract: The nucleoside analogue nelarabine, the prodrug of arabinosylguanine (AraG), has been known for decades to be effective against acute lymphoblastic leukaemias of T-cell (T-ALL), but not of B-cell (B-ALL) origin. The mechanisms underlying this lineage-specific drug sensitivity have remained elusive. Data from pharmacogenomics studies and from a panel of ALL cell lines revealed an inverse correlation of SAMHD1 expression and nelarabine sensitivity. SAMHD1 can hydrolyse and thus inactivate triphosphorylated nucle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…For example, targeting SAMHD1 by the Vpx protein has been found to benefit cytarabine therapy for hematological malignancies 39 . Moreover, SAMHD1 expression levels determine acute lymphoblastic leukemia cell response to nelarabine 40 .Therefore, these findings, along with our observations, suggest that SAMHD1 is a potential therapeutic target for improving chemotherapy efficacy in treating malignancies.…”
Section: Discussionsupporting
confidence: 70%
“…For example, targeting SAMHD1 by the Vpx protein has been found to benefit cytarabine therapy for hematological malignancies 39 . Moreover, SAMHD1 expression levels determine acute lymphoblastic leukemia cell response to nelarabine 40 .Therefore, these findings, along with our observations, suggest that SAMHD1 is a potential therapeutic target for improving chemotherapy efficacy in treating malignancies.…”
Section: Discussionsupporting
confidence: 70%
“…Nelarabine is the soluble prodrug of ara‐G, which is selectively cytotoxic to T leukaemic cells, likely due to their low endogenous SAMHD1 levels 29 . Initial early phase trials of nelarabine showed its efficacy as a single agent in paediatric relapsed/refractory T‐ALL, with neurotoxicity the most common dose‐limiting toxicity 30,31 .…”
Section: Nelarabinementioning
confidence: 99%